PLGA-PEG-ANG-2 Nanoparticles for Blood-Brain Barrier Crossing: Proof-of-Concept Study - Gina P. Hoyos-Ceballos; Barbara Ruozi; Ilaria Ottonelli; Federica Da Ros; Maria Angela Vandelli; Flavio Forni; Eleonora Daini; Antonietta Vilella; Michele Zoli; Giovanni Tosi; Jason T. Duskey; Betty L. López-Osorio (MDPI AG, 2020)
The treatment of diseases that affect the central nervous system (CNS) represents a great research challenge due to the restriction imposed by the blood−brain barrier (BBB) to allow the passage of drugs into the brain. However, the use of modified nanomedicines engineered with different ligands that can be recognized by receptors expressed in the BBB offers a favorable alternative for this purpose. In this work, a BBB-penetrating peptide, angiopep-2 (Ang−2), was conjugated to poly(lactic-co-glycolic acid) (PLGA)-based nanoparticles through pre- and post-formulation strategies. Then, their ability to cross the BBB was qualitatively assessed on an animal model. Proof-of-concept studies with fluorescent and confocal microscopy studies highlighted that the brain-targeted PLGA nanoparticles were able to cross the BBB and accumulated in neuronal cells, thus showing a promising brain drug delivery system.